Turkish Form Validity and Reliability of the Childbirth Expectations and Experiences Scale - Ayşegül Muslu; Emre Yanıkkerem (Dokuz Eylul University, 2020)
Background: It is very important to determine the expectations and experiences of birth in increasing the satisfaction of women. Objectives: The aim of this study was to perform the validity and reliability study of the Turkish form of the Childbirth Expectations and Experiences Scale (CEES). Methods: The study carried out 360 pregnant women who applied for giving birth to a hospital in Manisa, who had research criteria and agreed to participate in the study. This scale was developed in 2008 by Tanglakmankhong and consists of two parts. The first section (CEES-1) evaluates the expectations regarding delivery before birth, while (CEES-2) evaluates the situation of reaching expectations after delivery. Analyzes were done by taking into consideration the original scale of the scale, language, content and construct validity were used to test the validity of the scale. Student T test was used to calculate the difference between the second part of the scale and satisfaction with delivery. The reliability analysis of this scale was performed with the Cronbach alpha coefficient. Results: The language validity of this scale was requested by 10 experts to translate the English scale form into Turkish and the content validity was made by refining the expressions according to the opinions of the five associate professors. The Cronbach's alpha value of the CEES was found to be .891. Overall, 81.7% of the women who participated in the study were met and 32.1% of the expectations that they did not expected were met. Conclusion: In this study, Turkish form of CEES was found to be valid and reliable and it was found to be applicable for Turkish society. This scale can be used to determine the expectations of women in childbirth and to meet these expectations in birth clinics.